2011
DOI: 10.1158/1078-0432.ccr-10-2640
|View full text |Cite
|
Sign up to set email alerts
|

Human Monoclonal Antibodies to Sialyl-Lewisa (CA19.9) with Potent CDC, ADCC, and Antitumor Activity

Abstract: Purpose: The carbohydrate antigen sialyl-Lewis a (sLe a ), also known as CA19.9, is widely expressed on epithelial tumors of the gastrointestinal tract and breast and on small-cell lung cancers. Since overexpression of sLe a appears to be a key event in invasion and metastasis of many tumors and results in susceptibility to antibody-mediated lysis, sLe a is an attractive molecular target for tumor therapy. Experimental Design: We generated and characterized fully human monoclonal antibodies (mAb) from blood ly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 16 publications
(20 reference statements)
3
70
0
1
Order By: Relevance
“…More recently, human SLe a mAbs were produced using a patient vaccination strategy that showed specific binding to SLe a and exhibited ADCC, CDC, and antitumor activity in a xenograft model (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, human SLe a mAbs were produced using a patient vaccination strategy that showed specific binding to SLe a and exhibited ADCC, CDC, and antitumor activity in a xenograft model (21).…”
Section: Introductionmentioning
confidence: 99%
“…No studies, to date, have shown tumor eradication of 10-day established tumors and liver metastases. SC104 inhibited tumor growth in vivo, but was more effective in the tumor prevention model and only worked in the therapeutic models in combination with 5-FU/leucovorin (21). The humanized SC104 (NCT01447732) currently in phase I/II trials (SC104/CEP-37250/KHK2804) has been defucosylated for enhanced effector functions.…”
mentioning
confidence: 99%
“…The Fc region was consequently converted from murine IgG2a to human IgG1. Fc region of human IgG1 can enhance FccRIII-mediated antibody-dependent cell-mediated cytotoxicity (ADCC) and complement dependent cytotoxicity (CDC), and can be the most suitable for therapeutic use against pathogen and cancer cells (Sawada et al 2011). The effect of ADCC and CDC of the 2F12 antibody on hepatocellular carcinoma cells needs to be further confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Conjugates of protein toxins to anti-IgG secondary reagents have been reported, either chemical conjugates to ricin A (Till et al 1988) or pokeweed antiviral protein (Weltman et al 1987) or genetic fusions of Pseudomonas exotoxin A to an antikappa single-domain antibody (Kellner et al 2011) or to the Z domain of Staphylococcus protein A (Mazor et al 2007). Commercially available secondary antibodies conjugated to the ribosome-inactivating protein saporin have been widely used to confirm antibody internalization (Kohls and Lappi 2000;Nguyen et al 2006;Fransson and Borrebaeck 2009;Sawada et al 2011). Antibodies can be incubated with saporin-conjugated antimouse, antirat, or antihuman reagents and then incubated with tumor cells for 3-4 days.…”
Section: Screening For Intracellular Toxin Deliverymentioning
confidence: 99%